Identification of vulnerable non-culprit lesions by coronary computed tomography angiography in patients with chronic coronary syndrome and diabetes mellitus - Zhao, Jia; Zhang, Hong; Liu, Chang; Zhang, Ying; Xie, Cun; Wang, Minghui; Wang, Chengjian; Wang, Shuo; Xue, Yuanyuan; Liang, Shuo; Gao, Yufan; Cong, Hongliang; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Among patients with diabetes mellitus (DM) and chronic coronary syndrome (CCS), non-culprit lesions (NCLs) are responsible for a substantial number of future major adverse cardiovascular events (MACEs). Thus, we aimed to establish the natural history relationship between adverse plaque characteristics (APCs) of NCLs noninvasively identified by coronary computed tomography angiography (CCTA) and subsequent MACEs in these patients. Methods Between January 2016 and January 2019, 523 patients with DM and CCS were included in the present study after CCTA and successful percutaneous coronary intervention (PCI). All patients were followed up for MACE (the composite of cardiac death, myocardial infarction and unplanned coronary revascularization) until January 2022 and the independent clinical event committee classified MACE as indeterminate, culprit lesion (CL) and NCL-related. The primary outcome was MACE arising from untreated NCLs during follow-up. The association between plaque characteristics detected by CCTA and primary outcome was determined by Marginal Cox proportional hazard regression. Results Overall, 1248 NCLs of the 523 patients were analyzed and followed up for a median of 47 months. The cumulative rate of indeterminate, CL and NCL-related MACEs was 2.3%, 14.5% and 20.5%, respectively. On multivariate analysis, NCLs associated with recurrent MACEs were more likely to be characterized by a plaque burden >70% [hazard ratio (HR), 4.35, 95% CI: 2.92-6.44], low-density non-calcified plaque (LDNCP) volume >30mm3 (HR: 3.40, 95% CI: 2.07-5.56), a minimal luminal area (MLA) <4mm2 (HR: 2.30, 95% CI: 1.57-3.36) or combination of three APCs (HR: 13.69, 95% CI: 9.34-20.12, p<0.0001), than those not associated with recurrent MACEs. The sensitivity analysis regarding all indeterminate MACEs as NCL-related ones demonstrated similar results. Conclusions Half of MACEs occurring during follow-up were attributable to recurrence at the site of NCLs in DM patients who presented with CCS and underwent PCI. NCLs responsible for unanticipated MACEs were frequently characterized by a large plaque burden and LDNCP volume, a small MLA, or combinations of these APCs, as determined by CCTA.